(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Changeri ghrita is a medicated ghee formulation, mentioned in Grahani rog chikitsa. Sneha murchana is a procedure prior to Snehapaka. Snehapaka and Murchana bring changes in Sneha. Materials and Methods: Two batches of Changeri ghrita prepared using Murchita and Amurchit ghrita. Prepared Ghrita subjected to physico-chemical analysis. Result and Discussion: Specific gravity increased in Murchita ghrita. Refractive index, viscosity, saponification value, iodine values were increased. While acid value is decreased. Peroxide value is slightly increased. Unsaponifiable matter remains unchanged. There was change in organoleptic properties after Murchana. Physico-chemical changes have been occurring except in unsaponifiable matter and congealing point. Peroxide was present in both samples of Amurchit and Murchit Changeri ghrita. Saponification value was increased in Murchit Changeri Ghrita Conclusion: It can be concluded that antioxidants were added during Murchana. Murchana maintains stability of lipid preparation and offer good health impact, increases palatability.